Aspects of biculturality in the style of B. Daldenbai’s «Zheltoqsan tolquy» Symphony - Раимкулова, Актоты; Момбек, Алия (Pedagogy and Psychology, 2020)
The study aims to identify biculturalism in the symphonic style of a representative of a younger generation of composers, a student of G. Zhubanova B. Daldenbay. As an example, we took the most performed of his symphonic compositions – the Symphony “Zheltoqsan tolquy” (“The December Wave”). Based on the musical-style analysis, the author reveals the features of compositional thinking that semiotically unite different cultural elements into a single sign-system. The issue of the applicability of the concepts «synthesis,» «dialogue,» and «clash of cultures» concerning the work under study was brought up for discussion. B. Daldenbai thinks simultaneously in two systems (traditional Kazakh and Western), freely operating with the methods of both the European and the ethnic Kazakh traditions. This manifests in structural, thematic, and genre aspects. The duality is justified both by the composer’s creative biography, who received a European education, and the subject of his reflections – the Kazakh people’s fate in the 20th century. Having almost lost the fundamentals of native culture – traditions and language – the people, who adopted the achievements of European civilization, retained their Eurasian outlook and, through it, the spiritual roots of the ethnos. Biculturalism is explained by unique aesthetic attitudes towards Eurasian thinking and cultural openness inherent in Kazakh art.